Economic Sustainability in the Absence or Near- Absence of Traditional Risk Mitigation Mechanisms: An Insight into Credit Risk and Economic Sustainability of Microfinance Institutions (MFIs) in Zimbabwe - Jachi, Moses; Satande, Jonathan Tawanda; Bhibhi, Peter; Maganga, Nyasha; Mandongwe, Lucia; Katsane, Calvin; Dube, Phamela; Shumba, Godwin; Makumbe, Melania (The journal of contemporary issues in business and government, 2021)
The study confronted the notable decline in the number of microfinance institutions in Zimbabwe over the past two decades and the persistent poor financial performance trend charaterising the microfinance sub-sector, attributing the phenomenon to credit risk. Identifying how credit risk impacts financial performance of microfinance institutions and to examine the efficacy of strategies and tools microfinance institutions use when managing credit risk was the main aim of this study . Purposive and convenience sampling techniques were used to gather data from 12 microfinance institutions with relatively the biggest branch networks in Zimbabwe. The study established that credit risk, as measured through portfolio at risk (PAR) in microfinance institutions in Zimbabwe is mostly attributed to asymmetric information. The study also established that credit risk, which is managed through a combination of methods, mainly dynamic incentives, loss forecasting and group lending, negatively impacts financial performance and the subsequent economic sustainability of MFIs in Zimbabwe. The study recommends the implementation of credit scoring as a method of managing credit risk as it enables matching of products on offer with the specific individual client characteristics and risk profile. In light of the prevailing economic conditions, and the inherent absence of colleterals and guarantees to secure loans, the study informs current and potential industry player on the impact of credit risk management strategies being employed, and suggest credit scoring as a strategy that can potentially go a long way towards enhancing the most desired economic sustainability of MFIs in Zimbabwe.